The smart classroom: Exploring the impact of IoT on teaching dynamics using SVM algorithm - Sudrajat, Sudrajat (International Journal Labs, 2025)
This research explores the revolutionary impact of IoT in smart classrooms, focusing on how the interplay of advanced technology and pedagogical principles can enhance the learning environment. Central to this IoT system is a gateway connecting a suite of sensors: microphones for audio, cameras for security and interactive purposes, and environmental sensors for monitoring light, temperature, and air quality. Individual desk sensors further augment this setup, tracking student attendance and engagement. Through APIs, these hardware elements seamlessly interface with software, allowing SVM algorithms to process the data for personalized educational experiences. This innovative approach aligns with contemporary educational theories, promoting an interactive, adaptive, and student-centered learning atmosphere. The study's goal is to leverage these diverse sensors to transform traditional teaching methods, creating a dynamic, inclusive, and effective learning environment in the era of digital classrooms.